In silico characterization of chromosomally integrated blaCTX-M genes among clinical Enterobacteriaceae in Africa: insights from whole-genome analysis - Shawa, Misheck; Chambaro, Herman; Kamboyi, Harvey K.; Sulwe, Clement; Chizimu, Joseph Y.; Nasilele, Situmbeko J.; Ogata, Shohei; Samutela, Mulemba; Zorigt, Tuvshinzaya; Mudenda, Steward; Simbotwe, Manyando; Nsofwa, Mwamba; et al. (Frontiers in Microbiology, 2025)
Antimicrobial resistance (AMR) mediated by extended-spectrum β-lactamases (ESBLs) is a growing global concern, particularly among Enterobacteriaceae. The CTX-M-type ESBLs, encoded by the blaCTX-M gene, are of significant public health importance due to their high prevalence and broad geographic distribution. Typically located on plasmids and often co-occurring with other AMR genes, blaCTX-M contributes to multidrug resistance (MDR). However, increasing evidence suggests secondary chromosomal integration of blaCTX-M, sometimes alongside other resistance determinants. The extent and implications of this mechanism remain poorly characterized, especially in Africa, where genomic surveillance is limited. In this study, we retrieved 295 chromosomal sequences of Enterobacteriaceae of African origin from the GenBank and performed in silico predictions of blaCTX-M and other AMR genes. blaCTX-M-carrying sequences were further characterized by in silico multilocus sequence typing and genome annotation. Chromosomal insertions were identified through alignment with reference genomes. Overall, 47 of 295 sequences (15.9%) harbored the blaCTX-M gene, with the highest prevalence in Klebsiella pneumoniae (29/157, 18.5%), followed by Escherichia coli (13/72, 18.1%), Enterobacter spp. (4/38, 10.5%), and Shigella spp. (1/12, 8.3%). The most common allele was blaCTX-M-15 (31/47, 66.0%), followed by blaCTX-M-14 (12/47, 25.5%), blaCTX-M-55 (3/47, 6.4%), and blaCTX-M-27 (1/27, 3.7%). Co-occurrence of blaCTX-M with additional AMR genes was frequently observed, with integration events often associated with mobile genetic elements such as ISEcp1 and IS26. Notably, strains from the same hospital setting were phylogenetically related and shared sequence types and AMR gene profiles, suggesting local clonal dissemination. These findings reveal a notable presence of chromosomally integrated blaCTX-M among African Enterobacteriaceae, frequently in association with other resistance genes, thereby facilitating stable MDR propagation independent of plasmid maintenance. This evolutionary adaptation may have significant implications for the persistence and spread of MDR in clinical settings.